Enhancing Wastewater Treatment Efficiency Using MBBR: A Media Selection Approach - Mehdi Shamsabadizadeh; Nasser Mehrdadi; Akbar Baghvand (Journal of Advances in Environmental Health Research)
Background: Wastewater treatment is a critical environmental challenge, and moving bed biofilm reactor (MBBR) technology is an effective solution. The selection of appropriate biofilm media significantly impacts treatment efficiency, particularly in terms of organic matter and nutrient removal. This study aims to optimize media selection for MBBR systems to improve wastewater treatment. Methods: Three biofilm media types-K3, MB3, and K5-were evaluated based on key properties such as specific surface area (SSA), porosity, buoyancy, and economic feasibility. The analytical hierarchy process (AHP) was employed to assess and prioritize these criteria. Expert Choice software facilitated the analysis, followed by a laboratory-scale investigation to assess pollutant removal efficiency. Results: K5 media outperformed K3 and MB3 in terms of nitrogen removal (90%), chemical oxygen demand (COD) reduction (90%), biochemical oxygen demand (BOD) elimination (95%), and TSS removal (89%). K5 also demonstrated superior efficiency in pollutant removal while maintaining consistent pH regulation. K3 and MB3 displayed relatively lower performance, especially in nitrogen and COD removal. Conclusion: The study confirms that K5 media, selected using the AHP method, provides the highest treatment efficiency in MBBR systems. The AHP-based media selection process enhances the decision-making process, ensuring that economic and performance factors are adequately considered. Future studies should focus on scaling up the MBBR system with K5 media to further evaluate its long-term performance in real-world conditions.